A shiver in the leaves - Hughes, Luther (Poet) (A. Poulin, Jr. new poets of America series, 2022)
"Nestled against the backdrop of Seattle's flora, fauna, and cityscape, Luther Hughes' debut poetry collection wrestles with the interior and exterior symbiosis of a gay Black man finding refuge from the threat of depression and death through love and desire"--